ANALISIS POTENSI DAN KINERJA RETRIBUSI PASAR KABUPATEN WONOGIRI TAHUN 2008 – 2013 - Boas Benny Allan Kusuma (Universitas Slamet Riyadi, 2015)
This study aims to determine and analyze the potency and performance of the traditional market levy and its effect on The District Originally Revenue (PAD) in Wonogiri using secondary data (time series) from 2008 up to 2013. This Study concluded: First, the calculation of the potential is known that the potential market levies increased by an average of 1,92 percent per year with the potential of each type of levy that the general market potential retribution in the category